New Horizons in the Analysis of Control and Raising
X, 352 p.
Keywords: Raising and control have figured in every comprehensive model of syntax for forty years. Recent renewed attention to them makes this collection a timely one. The contributions, representing some of the most exciting recent work, address many fundamental research questions. What beside the canonical constructions might be subject to raising or control analyses? What constructions traditionally treated as raising or control might not actually be so? What classes of control must be recognized? How do tense, agreement, or clausal completeness figure in their distribution? The chapters address these and other relevant issues, and bring new empirical data into focus.